Breastfeeding in the period of the Covid-19 pandemic: a bibliographic review (Research, Society and Development, 2022)
This research was structured with the objective of analyzing in the scientific production if the transmission of the SARS-CoV-2 virus occurs in breastfeeding and the care during breastfeeding to avoid contamination, regarding the current COVID-19 pandemic. This is a narrative review of the literature based on a literature search carried out in February 2021 in the respective data sources: Medical Literature Analysis and Retrieval System Oline (Medline) and Scientific Electronic Library Online (SciELO). The possibility of transmission of SARS-CoV-2 through breast milk, between mother and child, is still lacking the evidence with greater robustness. Some studies analyzed show that there was no transmission of the virus through breast milk during breastfeeding, even if transmission occurred, it would be necessary to assess the long-term risks associated with its interruption. In the current circumstances, the World Health Organization (WHO) and other maximum bodies recommend breastfeeding, but for that, it is necessary to adhere to the basic hygiene guidelines so that transmission does not occur, since the nutritional and immunological benefits are essential for the growth and development of the neonate and baby. Therefore, infected puerperal women, suspected of COVID-19 or not, should be informed about the importance of continuing to provide their breast milk and that this objective can be achieved by adopting adequate hygiene and safety practices, recommended by the WHO, as breastfeeding improves the baby's immature immune system and strengthens defense mechanisms against infectious agents during and after the entire breastfeeding period.